IMPLEMENTATION OF MEDIA IMAGES IN LANGUAGE LEARNING STUDENTS AUTISM NONVERBAL IN PRIMARY SCHOOL ISLAM - Maryani, Mimin; Ilyas, Asmil; Rusli, Radif Khotamir (DIDAKTIKA TAUHIDI: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study used a qualitative approach with case study method. The main objective of this study was to determine how to identify students Autism, handling and anyone who deal with autistic students also how Language Learning in non-verbal autistic students in elementary school in Al-Jannah know the members of the body. Subjects in the study is a Class II student Autism Flower SD Al-Jannah. Retrieving data using such as observation sheets, interview and documentation used before in the field and for the field. Based upon the results obtained taxonomic analysis of valid data regarding student identification Autism, handling and language learning students with autism. Language learning by using media images, we can improve nonverbal autistic students to know the members of the body.